Tekniska möjligheter för artificiell spridning av renlav - Krekula, Karl Johan (2007)
Forestry and reindeer husbandry are entitled to use the same land for their operations. For this reason, conflicts occasionally arise between them. Soil scarification is a forestry operation which has a negative effect on the occurrence of reindeer lichen. Reindeer lichens are of crucial importance to reindeers and reindeer husbandry, especially in the winter when reindeers primarily feed on different lichen species (Cladina spp. and Cetraria spp.). Lichens are naturally spread through fragmentation and they are therefore suitable for artificial dispersal in the same manner. However, today there exist no technical system for dispersal of reindeer lichen. The objectives of this work was (i) to gather data and information on commercial techniques that possible could be used/adjusted to disperse fragments of reindeer lichens, and (ii) to make a dispersal test with the selected technique in the field. The field test was carried out at Anokangas in Pajala Municipality. A Stihl BG 85 blower device was used for the dispersal test. An all-terrain quad-bike, equipped with a flatbed boggie wagon, was used to carry the blower. To measure the distance that the lichens were spread and the amount of lichen spread, three tarpaulins were placed out at 10-metre intervals. On each tarpaulin, three wooden plates (measuring 25 × 25 cm; 0.0625 sq m) were placed, to measure the amount of reindeer lichen at a distance of one, two and three metres respectively from the track driven. From the sample plates the reindeer lichens were collected and the dry weight (105°C, 24 h) was determined. In all, driving and spread of lichens was replicated10 times and 28 measurements were made of the distance that spread lichens reached. The number of samples to determine moisture content was 84. The mean value of the distance that lichens were spread was 3.0 metres, with a relatively large variation. At a distance of 1 and 2 metres from the driving track (place of dispersal) the amount of spread lichen was approximately 8-10 g/sq m. At a distance of ...